Increasing Anaerobic and Aerobic Capacity Through Complementary Training for West Java Female Futsal Players in Preparation for the 21st National Sports Week - Fitri Rosdiana; Dikdik Zafar Sidik; Sindy Fitri Yunita (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
The purpose of this study is to reveal the application of strength training models to training methods (complementary training) that complement each other to maximize the process of developing and increasing anaerobic capacity as well as aerobic capacity. Physical training should be conducted gradually and continuously, without interruption. Likewise, there are stages in the physical components, specifically in strength training. This research is experimental. The population in this study consisted of West Java Female Futsal Players in Preparation for the 21st National Sports Week, totaling 16 individuals, and the sample taken was the entire population. Sampling technique with total sampling. The research instrument consisted of anaerobic and aerobic tests. The anaerobic power endurance test was conducted using the hurdle jump test, while the aerobic capacity test was conducted using the bleep test. Data analysis techniques using SPSS software. Statistical analysis showed a significant increase in anaerobic capacity (from 112 to 116 repetitions) and aerobic capacity (from 40,3 to 42,2 ml/kg/min) with p < 0,05. This study concludes that the implementation of complementary training  can increase anaerobic capacity and aerobic capacity in West Java Female Futsal Players in Preparation for the 21st National Sports Week.